2020
DOI: 10.3390/cells9040924
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell Secretome for Severe COVID-19 Infections: Premises for the Therapeutic Use

Abstract: From the end of 2019, the world population has been faced the spread of the novel coronavirus SARS-CoV-2 responsible for COVID-19 infection. In approximately 14% of the patients affected by the novel coronavirus, the infection progresses with the development of pneumonia that requires mechanical ventilation. At the moment, there is no specific antiviral treatment recommended for the COVID-19 pandemic and the therapeutic strategies to deal with the infection are only supportive. In our opinion, mesenchymal stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 29 publications
(33 reference statements)
0
126
0
3
Order By: Relevance
“…This study demonstrated safety but now efficiency need to be tested in large clinical trials. Bari et al also proposed that MSCs secretome could be formulated as a drug and administered by intravenous injection or after inhalation [42]. Since MSCs-derived extracellular vesicles are well known vector of growth factors and different type of RNA [43], MSCs secretome could constitute a new and smart approach for COVID19 pneumonia treatment, in particular for the ones requiring hospitalization in intensive care unit [42].…”
Section: Are Mesenchymal Stem Cells the Key Treatment For Covid-19?mentioning
confidence: 99%
See 1 more Smart Citation
“…This study demonstrated safety but now efficiency need to be tested in large clinical trials. Bari et al also proposed that MSCs secretome could be formulated as a drug and administered by intravenous injection or after inhalation [42]. Since MSCs-derived extracellular vesicles are well known vector of growth factors and different type of RNA [43], MSCs secretome could constitute a new and smart approach for COVID19 pneumonia treatment, in particular for the ones requiring hospitalization in intensive care unit [42].…”
Section: Are Mesenchymal Stem Cells the Key Treatment For Covid-19?mentioning
confidence: 99%
“…Bari et al also proposed that MSCs secretome could be formulated as a drug and administered by intravenous injection or after inhalation [42]. Since MSCs-derived extracellular vesicles are well known vector of growth factors and different type of RNA [43], MSCs secretome could constitute a new and smart approach for COVID19 pneumonia treatment, in particular for the ones requiring hospitalization in intensive care unit [42]. Moreover, gene expression profiling of mesenchymal stem cells showed that these cells are ACE2 and TMPRSS2 negative, making them a good cell target not influenced by SARS-CoV-2 infection [41].…”
Section: Are Mesenchymal Stem Cells the Key Treatment For Covid-19?mentioning
confidence: 99%
“…Additionally, it was reported that MSC secretome can be administered through inhalation and injection [18]. Preliminary studies suggest that EVs isolated from the cell secretome might also be efficient for the treatment of COVID-19 [20]. MSC-derived EVs were shown to produce similar effects as their parent cells; and they can be safely stored for long periods without losing function and have shown similar or better results than MSCs in animal models [19].…”
Section: Discussionmentioning
confidence: 99%
“…Because H7N9 and the SARS-CoV-2 share similar complications such as ARDS, lung failure, and fulminant pneumonia, MSC therapy can be a possible alternative for treating SARS-CoV-2 ( Chen J. et al, 2020 ). Even more interesting, MSCs are ACE2 negative and thus, not infected by the H7N9 virus ( Bari et al, 2020 ). Therefore, Atluri et al suggested that MSC-based treatment might be an ideal candidate for clinical trials, or at least a combination of treatment for SARS-CoV-2 patients ( Atluri et al, 2020 ).…”
Section: Potential Treatments For Coronavirus Disease 2019mentioning
confidence: 99%